Magnitude and Time Trend of Acute Respiratory Infections (Aris) Among Male School Students and Employees in Aleith - Al Jumaie, Saleh Abdulrazag; Almutairy, Faisal; Almuzaini, Mazen; Almuzaini, Ayed; Elawad, Mohammed; Dablool, Anas; Alyazidi, Faleh S (European Scientific Journal, ESJ, 2017)
A setting-based descriptive study was conducted to study magnitude and time trend of acute respiratory infections (ARIs) among male school students and employees in Aleith. Data about Acute Respiratory Infections (ARIs) among school students and employees in Aleith during the last three years were collected by reviewing monthly and annual reports in school health units. The proportion of acute reparatory infections in the last three years among male student and employees in Aleith was high in year 1435 which was 50.2%, followed by the year 1437 which was 47% and 1436 was 43.3%. The time distribution of acute respiratory infections illustrates that the percentage of infection occurred during Jumada-Al-Thani (21.9%) in the year 1435, Moharam and Rabi-Al-Thani (17.3%) in the year 1436 and Jumada-Al-Awwal (18%) in the year 1437. In the year 1435, acute respiratory infection among student was 811(63.7%) and among employees was 462 (36.3%); in the year 1436, the disease was 1177 (71.4%) in students while in employees was 471 (28.6%) and in the year1437, the percentage was 747(64.7%) in students and 408(35.3%) in employees. The high percentages of Acute Respiratory Infections (ARIs) occurred among primary school students was high 35.6%, 45.5% and 48.1% in the years 1435, 1436 and 1437 respectively. The peak of ARIs occurred during the year 1435 and the minimum proportion rate of cases was found in 1436. The study concluded that ARIs were still high and more frequent in winter months.